A Hermeneutical Study of 2 Corinthians 3:3 on The Nature of Christians - Lucas Tjong , Andrew; Prasetyo , Widi; Zalukhu, Eman (Theological Journal Kerugma, 2025)
This article aims to explore the theological meaning of the phrase “the epistle of Christ” in 2 Corinthians 3:3 in relation to the nature of Christians using a hermeneutical approach. Apart from that, this article will also discuss the application of this meaning in the lives of Christians in contemporary society. The hermeneutic approach applied includes three analyses: contextual analysis, grammatical analysis and lexical analysis. Based on the results of the excavation of 2 Corinthians 3:3, it was found that the nature of Christians is related to several things, including the calling of Christians as the epistle of Christ, their position and role, as well as their responsibility in bearing their existence as the epistle of Christ.